Empowerment of energy communities in minggir II village yogyakarta with iot-based biodigeser - Iswanto Iswanto; Andino Maseleno; Nia Maharani Raharja; Alfian Maarif; Muhammad Heri Zulfiar; Dhiya Uddin Rijalusalam; Reza Alayi; Rachmad Andri Atmoko; Irfan Ahmad (Peneliti Teknologi Teknik Indonesia, 2021)
In the Minggir Village, there is a Biogas School called Mitra Sarana Energi which is a biogas school UKM located in Minggir Village, Sendangagung Village, Minggir District, Sleman Regency, Special Region of Yogyakarta. The biogas school UKM has been conducting training activities on the manufacture and use of the biogas since 2012. Actually, the UKM has a large enough market opportunity to manage and sell the biogas. However, this opportunity brings consequences and problems, namely the lack of a touch of innovation from the biodigeser remote monitoring system. The implementation team tried to offer solutions to these problems with a touch of science and technology, namely through designing remote monitoring of gas levels and pressures with IoT technology. This monitoring tool system aims to monitor (monitoring) the process of making biogas production from organic waste by detecting gas levels produced from the biodigester, namely methane gas (CH4), carbon dioxide gas (CO2), hydrogen gas (H2), and gas pressure. The system is designed with an ESP32 controller board and MQ4, MQ8, MQ135 gas sensors and MPX10DP gas pressure sensors combined with the Internet of Things (IoT) feature which is then connected to the Blynk app on the cellphone, so that it can be monitored from anywhere and anywhere with the help of a connection. stable internet. The test results obtained that this tool is capable of measuring and monitoring data on monitoring levels of methane gas, CO2 gas, hydrogen gas and gas pressure.